Influence of Co-Curricular Activities on Senior Secondary School Students' Academic Achievement in English Language in Nigeria - Alabere Rabiat Ajoke; Md. Kamrul Hasan; Taye Fatima Sheu (Universitas Negeri Malang, 2015)
Abstract: This paper investigates the influence of co-curricular activities on Senior Secondary School Students' achievement in Nigeria. The variables to be considered are Press club and Literary and debating society, the involvement period, and their academic achievement. Eight out of 17 secondary schools are randomly selected with one hundred students from each school. The questionnaires for the data collection are on students' personal data and twelve questions on press club and literary and debating society. The mock examination results show that there is a positive significant influence in co-curricular activities on senior secondary school students' academic achievement in English. Key Words: co-curricular activities, academic achievement, english language teaching Abstrak: Tujuan penelitian ini adalah untuk mengetahui pengaruh kegiatan ko-kurikuler terhadap prestasi Siswa pada Sekolah Menengah Atas di Nigeria. Variabel yang harus dipertimbangkan adalah klub pers dan sastra dan himpunan debat, pada periode keterlibatan, dan prestasi akademik . Delapan dari 17 sekolah menengah yang dipilih secara acak dengan seratus siswa dari masing-masing sekolah. Kuesioner untuk pengumpulan data adalah data pribadi siswa dan dua belas pertanyaan tentang klub Pers dan Sastra dan himpunan debat. Hasil test buatan menunjukkan bahwa ada pengaruh positif yang signifikan dalam kegiatan ko-kurikuler terhadap prestasi akademik siswa sekolah menengah atas dalam pelajaran bahasa Inggris. Kata kunci: kegiatan ko-kurikuler, prestasi akademik, pengajaran Bahasa Inggris